Struktur Makna Ambiguitas Partikel ‘No’ dalam Percakapan Bahasa Jepang pada Siswa Level 1C di Pandan College - I Gusti Ayu Made Intan Novitasari; Ketut Widya Purnawati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2020)
This research aims to describe the ambiguity meaning structure of ‘no’ particle in Japanese conversation of level 1C students at Pandan College. This research belongs to qualitative descriptive. The subject of this research is 1C Level students of Pandan College year 2019, while the object of this research is ‘no’ particle used in student’s Japanese conversation. The data collection method used is the attentive observation method with data recording and transcription techniques. The data analysis method used is the interlingual identity method. The results of this research are : (1) the ‘no’ particle used in the Japanese conversation of level 1C students is divided into two structural patterns meaning ambiguity, there are prenominal double possessives and prenominal adjective-possessives; and (2) the possessive relations of the 'no' particle can be expressed as possession, part-whole, location, and quantity.